Dropping Word Education Game Through Female Students’ Vocabulary: An Experimental Study - Musdalifah Musdalifah; Robiatul Romdaniya (JOEY: Journal of English Ibrahimy, 2022)
Dropping words is a game that is used to make it easier for someone to learn vocabulary, this game is also used by all levels and ages because this game of dropping words is quite easy to play. The discussion of this research focuses on how much the increase in female students understanding by using dropping words education games in learning English vocabulary and to determine the effectiveness of dropping word education games on female students’ mastery of English vocabulary at SMP Ibrahimy 2 Sukorejo. This research is a quantitative research using a quasi-experimental method. The sampling technique in this study used purposive sampling. The number of samples used as many as 25 respondents. The data in this study used a pre-test and post-test as well as a questionnaire which was analyzed using SPSS version 19. Based on the results of the study, it can be concluded that first, the level of understanding of female students in the use of dropping word education games in learning English vocabulary can be seen from the final score (post-test) for the experimental group of 80.50 while the post-test of the control group is 67.17. Has a difference in the value of 13.33. Second, there is effectiveness in teaching vocabulary using dropping word education games to female students. This can be seen from the value of the t-test Pair 1 and Pair 2 obtained the value of Sig. of 0.000 < 0.05.